MAKNA SIMBOLIK SEBUTAN “AANG/AAH” DI KALANGAN UMAT ISLAM KECAMATAN GEKBRONG, CIANJUR (SUATU TELAAH PERSPEKTIF INTERAKSIONISME SIMBOLIK) - Wiwin Zein (Penamas, 2018)
The purpose of this study was to determine the symbolic meaning of name "Aang /Aah" among Muslims in Gekbrong subdistrict, Cianjur district, West Java Province. The results of study showed that the symbolic meaning of name "Aang/Aah", for Muslims in Gekbrong subdistricts have symbolic meanings that subjectively, depending on to whom the name was attached. But the symbolic meaning of name "Aang/Aah" have general meaning, idest represents figure or people who own/control of broad and deep religious knowledge, charismatic (authoritative), influential, pious, and had a high position/noble. The symbolic meaning of name "Aang/Aah" that are general was permanently, to anyone that name was attached, it will has similar meaning. Keywords : symbolic, interactionism, Gekbrong, Aang, Aah.